Clusterization and strong coupled-channels effects in deuteron interaction with 9Be nuclei. (3rd September 2019) - Urazbekov, B A; Denikin, A S; Lukyanov, S M; Itaco, N; Janseitov, D M; Mendibayev, K; Burjan, V; Kroha, V; Mrazek, J; Trzaska, W H; Harakeh, M N; Etasse, D; et al.
Abstract: Angular distributions of protons, deuterons, tritons and alpha particles emitted in the d + 9 Be reaction at E lab  = 19.5 and 35.0 MeV have been measured. The elastic scattering channel is analysed in the framework of both the optical model and the coupled-channel approach. The interaction potential of the d + 9 Be system is calculated in the framework of the Double-Folding model using the α  +  α  +  n three-body wave function of the 9 Be nucleus. The ( d, p ) and ( d, t ) one-nucleon-transfer reactions are analysed within the coupled-reaction-channel approach. The spectroscopic amplitudes for the different nuclear cluster configurations are calculated. Differential cross sections for the reaction channel 9 Be( d, α ) 7 Li are calculated including all possible reaction mechanisms within the coupled-reaction-channel method. Corresponding contributions to the cross sections are analysed.